THE STUDY OF THE FATIGUE CHARACTERISTICS OF BITUMINOUS MIXTURES CONTAINING DEFFERENT AGGREGATE TYPES - Al Azemi, Fahad (IRC, 2016)
Main goal of this research is to determine the fatigue properties of bituminous mixture, by using Limestone and Granite as an aggregate, which were obtained through planned tests on the lab. The objective of this work is to understand the fatigue phenomenon in bituminous mixtures, in addition to investigating the numerical relationship between the properties of aggregates on the behavior and the performance of bituminous mixtures. The performance of a bituminous mixture is greatly influenced by the properties of the aggregate used